Changing Agendas in Australian Indigenous Policy: Federalism, Competing Principles and Generational Dynamics. Issue 2 (18th June 2013) - Sanders, Will
<x xml:space="preserve">Abstract</x> This paper identifies two periods of punctuated change in the content and style of Australian Indigenous policy in the last fifty years. It also identifies a third period in which attention to Indigenous policy was heightened through the nationalisation of land issues already well‐established on the agendas of sub‐national jurisdictions. The paper relates all three periods to the changing federal institutions of Australian Indigenous policy, with the Commonwealth slowly exploring its post‐1967 role as a national government in Indigenous affairs. In later sections, the paper identifies some more conceptual bases of changing policy agendas, through ideas of the competing principles of equality, choice and guardianship and the generational moral dynamics of Indigenous affairs.